A method for improving the thermal cycle reliability of directly bonded aluminum-copper ceramic substrates
By performing surface treatment and resistance diffusion welding on the directly bonded aluminum-copper ceramic substrate, the copper-aluminum reaction diffusion depth and etching structure are controlled, and the problem of reduced bonding strength and reliability of the substrate during the heat resistance cycle is solved, achieving high reliability and suitable for large-scale production.
Patent Information
- Application Number
- CN202411290675.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-09-14
AI Technical Summary
Directly bonded aluminum-copper ceramic substrates are prone to copper-aluminum sintering to form eutectic phase bonding during the heat resistance cycle, resulting in a reduction in bonding strength and thermal cycle reliability. It is difficult for traditional methods to ensure the high reliability of the substrate during mass production.
By performing surface roughness treatment on the double-sided bonded aluminum ceramic substrate and high-purity copper sheet, sandwich-type superposition and pressurized diffusion welding between copper and aluminum in a resistive diffusion welding machine, the reaction diffusion depth and etching structure are controlled, and the joint force and stress release points between copper and aluminum are improved.
It significantly improves the heat-resistant cycle reliability of directly bonded aluminum-copper ceramic substrates, meets the copper-aluminum-metal peel strength requirements of commercial substrates, and simplifies the process and is suitable for large-scale production.
Smart Images

Figure CN119153341B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of semiconductor technology, in particular to a method for improving the heat-resistant cycle reliability of a directly bonded aluminum-copper ceramic substrate. Background Art
[0002] In recent years, direct-bonded copper-ceramic substrates (DCB) and direct-bonded aluminum-ceramic substrates (DBA) have developed rapidly because of their pure interfaces and lower interface thermal resistance than traditional polymer-based materials. However, in terms of temperature cycle resistance reliability, direct-bonded copper-ceramic substrates are prone to copper-ceramic delamination failure. The yield strength and elastic modulus of aluminum are lower than those of copper, and the cumulative thermal stress of the aluminum-ceramic interface is lower than the cumulative stress of the copper-ceramic interface. Therefore, direct-bonded aluminum-ceramic substrates are usually more resistant to temperature cycles than direct-bonded copper-ceramic substrates. Secondly, the plastic deformation trend of aluminum is smoother than that of copper, which indicates that with the increase of temperature, the hardening rate of aluminum is lower than that of copper. However, the current carrying capacity of copper is much greater than that of aluminum. Due to the wettability limitation of the aluminum surface, direct-bonded aluminum-ceramic substrates usually need to be plated with nickel / nickel-gold to meet the welding requirements, which increases the commercial cost.
[0003] A new type of direct bonded aluminum-copper ceramic substrate (DBAC) combines the advantages of direct bonded aluminum-ceramic substrate and direct bonded copper-ceramic substrate and has attracted much attention. Its surface is copper and it usually does not need plating for commercial use. It also has advantages in thermal conductivity and electrical conductivity. During long-term temperature cycles, the aluminum layer acts as an intermediate layer to buffer and support the plastic deformation of copper. Therefore, DBAC has stronger heat-resistant cycle reliability. However, when copper and aluminum are sintered to form eutectic phase bonding, the formation of aluminum / copper intermetallic compounds will lead to reduced bonding strength and thermal cycle reliability, and lose the high reliability advantage of DBAC. Usually, the reaction temperature is lowered, the insulation time is shortened, and the amount of copper-aluminum intermetallic compounds generated is controlled. However, when large-scale substrate stacking is used, excessively lowering the temperature and shortening the insulation time will cause poor substrate wettability and low substrate bonding yield. Therefore, it is necessary to develop a method for mass production of high-reliability direct bonded aluminum-copper ceramic substrates.
[0004] In order to overcome the defects of the prior art, the present invention provides a method for improving the heat-resistant cycle reliability of a directly bonded aluminum-copper ceramic substrate. Summary of the invention
[0005] The object of the present invention is to provide a method for improving the heat-resistant cycle reliability of a directly bonded aluminum-copper ceramic substrate, so as to solve the problems raised in the prior art.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for improving the heat cycle reliability of a directly bonded aluminum-copper ceramic substrate comprises the following steps:
[0008] Step 1: Take a double-sided bonded aluminum ceramic substrate, perform surface roughness treatment, clean and dry it, and record it as substrate A, and the surface roughness Ra is 0.8mm-1.2μm; take a high-purity copper sheet, perform surface roughness treatment, clean and dry it, and record it as copper sheet B, and the surface roughness Ra is 1.0mm-2.0μm;
[0009] Step 2: The substrate A and copper sheet B prepared in step 1 are stacked in the form of a copper sheet B-substrate A-copper sheet B sandwich, placed in a resistance diffusion welding machine, and voltage is applied to the surface of the copper sheet B, with a vertical pressure of 5 to 10 MPa. When the temperature of the copper sheet B reaches 350°C to 430°C, the voltage is maintained for 20 to 60 minutes, and then pressure is applied at a heating rate of 10 to 25°C / min until the temperature of the copper sheet B reaches 450°C to 557°C, the voltage is maintained for 10 to 60 minutes, the voltage is cut off, and the substrate is cooled to obtain a directly bonded aluminum-copper ceramic substrate;
[0010] Step 3: Take the directly bonded aluminum-copper ceramic substrate prepared in step 2 and carry out surface laying of photosensitive film, pattern exposure, development, metal layer etching, film removal, laser slicing, cleaning and drying.
[0011] Wherein, in step 1, the ceramic thickness of the double-sided bonded aluminum ceramic substrate is 0.635 mm or 0.38 mm or 1.0 mm, the thickness of the aluminum layer is 0.2-0.8 mm, and the thickness difference of the double-sided bonded aluminum layer is less than 0.2 mm.
[0012] In step 1, the double-sided bonded aluminum ceramic substrate is subjected to surface roughness treatment, firstly subjected to grinding treatment or sandblasting treatment, and then the treated double-sided bonded aluminum ceramic substrate is placed in a sodium hydroxide solution with a temperature of 35-50° C. and a concentration of 8-20% for cleaning for 3-5 minutes, then transferred to a nitric acid solution with a concentration of 3-5% for cleaning for 1-3 minutes, taken out and placed in pure water for ultrasonication for 1-5 minutes, and dried.
[0013] The high-purity copper sheet has a thickness of 0.2-0.8 mm and is subjected to surface roughness treatment by first grinding or sandblasting, and then the treated high-purity copper sheet is placed in a sulfuric acid solution with a concentration of 5-10% for cleaning and drying.
[0014] The heating rate of the copper sheet B caused by pressurization in step 2 is 10-25°C / min.
[0015] The depth of the reaction diffusion layer of copper and aluminum in the directly bonded aluminum-copper ceramic substrate prepared in step 2 is 10 to 25 μm.
[0016] In step 3, the etching solution used for etching the metal layer is prepared by dissolving ferric chloride and hydrochloric acid in pure water, wherein the concentration of ferric chloride is 150-500 g / L and the concentration of hydrochloric acid is 20-60 g / L; the cleaning adopts a sulfuric acid solution with a concentration of 3-5%, and ultrasonic cleaning is performed for 3-5 minutes.
[0017] In step 3, the metal layer is etched to obtain an inverted trapezoidal etched groove, wherein the distance between the bottom edge of the aluminum layer and the edge of the ceramic is 0.1 to 0.3 mm, and the distance between the bottom edge of the copper layer and the top edge of the aluminum layer is 0.1 to 0.5 mm. Compared with the prior art, the beneficial effects of the present invention are:
[0018] 1. The directly bonded copper-aluminum ceramic substrate formed by the present invention controls the reasonable surface roughness range by double-sided bonding aluminum ceramic substrate aluminum surface treatment, copper surface treatment, cleaning and other methods, improves the bite force between copper and aluminum formed by pressurized diffusion welding, and meets the peeling strength requirements between copper and aluminum metals of commercial substrates;
[0019] 2. By controlling the reaction temperature and pressure, the diffusion depth of copper-aluminum reaction can be reasonably controlled, and the size of the etched aluminum layer is 0.1-0.5mm larger than the size of the copper layer. The stress release point is created, which can significantly improve the temperature cycle resistance reliability between copper and aluminum;
[0020] 3. The process is simple, the surface of the substrate is copper, and it has good commercial substrate characteristics. It meets the high heat dissipation and large current carrying requirements of the substrate package and is easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a flow chart of the present invention;
[0022] Figure 2 This is the EDS line scanning copper-aluminum reaction diffusion depth test in the embodiment;
[0023] Figure 3 The size of the metal layer prepared for direct bonding of the aluminum-copper ceramic substrate pattern in step 3 of the embodiment;
[0024] Figure 4 This is a sample image of the aluminum-copper ceramic substrate after etching and slicing in step 3 of the embodiment;
[0025] Figure 5 The size of the metal layer prepared by directly bonding the aluminum-copper ceramic substrate pattern in step 3 of comparative example 1;
[0026] Figure 6 This is the EDS line scanning copper-aluminum reaction diffusion depth test in Comparative Example 2;
[0027] Figure 7 This is an ultrasonic scan of the sample prepared in the embodiment after 1000 thermal cycles;
[0028] Figure 8 This is the ultrasonic scanning diagram of the sample prepared in Comparative Example 1 after 1000 thermal cycles;
[0029] Fig. 9 This is the ultrasonic scanning diagram of the sample prepared in Comparative Example 2 after 1000 thermal cycles. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Reference Figure 1-9 As shown, the present invention provides the following technical solutions.
[0032] The double-sided bonded aluminum ceramic substrate in the experiment has a size of 138×190mm and comes from Jiangsu Fulehua Semiconductor Technology Co., Ltd. The thickness of the ceramic is 0.635mm, the thickness of the double-sided bonded aluminum plate is 0.2mm, the aluminum purity is >99.99%, and the aluminum coverage area is 135×185mm;
[0033] The thickness of the high-purity copper sheet is 0.5 mm, the size is 135×185 mm, and the copper purity is >99.99%.
[0034] Embodiment: This embodiment provides a method for improving the heat cycle reliability of a directly bonded aluminum-copper ceramic substrate. Figure 1 Flowchart, including the following steps:
[0035] Step 1: Take a double-sided bonded aluminum ceramic substrate and polish it with a 1500 mesh non-woven roller, then place it in a sodium hydroxide solution with a temperature of 40°C and a concentration of 10% for cleaning for 4 minutes, transfer it to a nitric acid solution with a concentration of 4% for cleaning for 2 minutes, and finally take it out and place it in pure water for ultrasonic treatment for 3 minutes, and dry it, which is recorded as substrate A, and the surface roughness Ra is 1.0μm; take a high-purity copper sheet and polish it with a 1200 mesh non-woven roller, then place it in a sulfuric acid solution with a concentration of 8% for cleaning, and dry it, which is recorded as copper sheet B, and the surface roughness Ra is 1.5μm;
[0036] Step 2: The substrate A and copper sheet B prepared in step 1 are stacked in the form of a copper sheet B-substrate A-copper sheet B sandwich, placed in a resistance diffusion welding machine, and voltage is applied to the surface of the copper sheet B, with a vertical pressure of 8 MPa. When the temperature of the detected copper sheet B reaches 380°C, the voltage is maintained for 30 minutes, and then the pressure is increased at a heating rate of 10°C / min until the temperature of the detected copper sheet B reaches 500°C, the voltage is maintained for 15 minutes, the voltage is cut off, and the substrate is cooled to obtain a directly bonded aluminum-copper ceramic substrate. EDS line scanning of the copper-aluminum reaction diffusion depth is performed, such as Figure 2 As shown, the interface is pure, no other elements are obtained, and the diffusion depth is 15 μm;
[0037] Step 3: Take the directly bonded aluminum-copper ceramic substrate prepared in step 2, lay a photosensitive film on the surface, expose the pattern, develop, and put it into the etching solution to etch the metal layer to obtain an inverted trapezoidal etching groove, such as Figure 3 As shown, the distance between the bottom edge of the aluminum layer and the edge of the ceramic is 0.25 mm, and the distance between the bottom edge of the copper layer and the top edge of the aluminum layer is 0.37 mm; the film is removed, laser sliced, placed in a 4% sulfuric acid solution, and ultrasonically cleaned for 4 minutes, as shown Figure 4 shown.
[0038] The etching solution for etching the metal layer is prepared by dissolving 350 g / L ferric chloride and 40 g / L hydrochloric acid in pure water.
[0039] Comparative Example 1: In Comparative Example 1, the surface roughness of the high-purity copper sheet and the double-sided bonded aluminum ceramic substrate in the raw material was not controlled, and the specific steps were as follows:
[0040] Step 1: The double-sided bonded aluminum ceramic substrate was placed in a 10% sodium hydroxide solution at a temperature of 40°C for 4 minutes, then transferred to a 4% nitric acid solution for 2 minutes, and finally taken out and placed in pure water for 3 minutes of ultrasonic treatment, and dried, which was recorded as substrate A1, and the surface roughness Ra was 0.5μm; a high-purity copper sheet was placed in a sulfuric acid solution with a concentration of 8% for cleaning, and dried, which was recorded as copper sheet B1, and the surface roughness Ra was 0.8μm;
[0041] Step 2: The substrate A1 and the copper sheet B1 prepared in step 1 are stacked in the form of a sandwich of copper sheet B1-substrate A1-copper sheet B1, and placed in a resistance diffusion welding machine. Voltage is applied to the B surface of the copper sheet, and the vertical pressure is 9 MPa. When the temperature of the detected copper sheet B reaches 400°C, the voltage is maintained for 30 minutes. Then, pressure is applied at a heating rate of 10°C / min until the temperature of the detected copper sheet B reaches 510°C. The voltage is maintained for 10 minutes, and the voltage is cut off and cooled to obtain a directly bonded aluminum-copper ceramic substrate. EDS line scanning is performed for the copper-aluminum reaction diffusion depth. The interface is pure, no other elements are obtained, and the diffusion depth is 18 μm.
[0042] Step 3: Take the directly bonded aluminum-copper ceramic substrate prepared in step 2, lay a photosensitive film on the surface, expose the pattern, develop, and put it into the etching solution to etch the metal layer to obtain an inverted trapezoidal etching groove, wherein the distance between the bottom edge of the aluminum layer and the edge of the ceramic is 0.2 mm, and the distance between the bottom edge of the copper layer and the top edge of the aluminum layer is 0.2 mm; remove the film, laser slice, place it in a 4% sulfuric acid solution, and ultrasonically clean it for 4 minutes. Figure 5 shown.
[0043] The etching solution is prepared by dissolving 350g / L ferric chloride and 40g / L hydrochloric acid in pure water.
[0044] Comparative Example 2: Comparative Example 2 adopts the conventional direct pressing and sintering method to prepare a direct-coated aluminum-copper ceramic substrate, and the specific steps are as follows:
[0045] Step 1: Take a double-sided bonded aluminum ceramic substrate and polish it with a 1200-mesh non-woven roller, then wash it in a 12% sodium hydroxide solution at a temperature of 45°C for 4 minutes, transfer it to a 4% nitric acid solution for cleaning for 2 minutes, and finally take it out and ultrasonicate it in pure water for 3 minutes, and dry it to be recorded as substrate A2, and the surface roughness Ra is 1.2μm; take a high-purity copper sheet and polish it with a 1500-mesh non-woven roller, then wash it in a 10% sulfuric acid solution, and dry it to be recorded as copper sheet B2, and the surface roughness Ra is 1.4μm;
[0046] Step 2: The substrate A2 and the copper sheet B2 prepared in step 1 are stacked in the form of a copper sheet B2-substrate A2-copper sheet B2 sandwich, and are isolated by graphite paper with a boron nitride coating on the surface, the boron nitride coating thickness is 10 μm, the graphite paper thickness is 0.2 mm, and they are clamped and sintered under vacuum conditions with a vacuum degree of 0.0005 Pa, a vertical pressure of 9 MPa, a temperature of 560°C, a holding time of 60 min, and cooled with the furnace to obtain a directly coated aluminum-copper ceramic substrate; after slicing, EDS line scanning is performed to obtain a copper-aluminum reaction diffusion layer depth of 35 μm. Figure 6 shown.
[0047] Step 3: Lay a photosensitive film on the surface of the aluminum-copper ceramic substrate directly coated with the aluminum-copper substrate prepared in step 2, perform pattern exposure, development, and place the substrate in an etching solution to etch the metal layer to obtain an inverted trapezoidal etching groove, wherein the distance between the bottom edge of the aluminum layer and the edge of the ceramic is 0.28 mm, and the distance between the bottom edge of the copper layer and the top edge of the aluminum layer is 0.40 mm; remove the film, perform laser slicing, place the substrate in a 4% sulfuric acid solution, and perform ultrasonic cleaning for 4 minutes.
[0048] The etching solution is prepared by dissolving 350g / L ferric chloride and 40g / L hydrochloric acid in pure water.
[0049] Inspection and testing
[0050] The directly bonded aluminum-copper ceramic substrates obtained in Example 1 and Comparative Example 2 were subjected to a thermal cycle test, with 15 minutes of heat preservation at -55°C and 15 minutes of heat preservation at 150°C as one cycle process, and the high and low temperature switching time in the middle was less than 30 seconds. After 1000 cycles, the samples were taken out for ultrasonic scanning. The scans before the test were all good. The test results are as follows: Figure 7-9 shown.
[0051] Conclusion: Comparison Figure 7-9It can be seen that the directly bonded aluminum-copper ceramic substrate prepared in the embodiment did not fail after 1000 thermal cycles, meeting the requirements of commercial packaging substrates; Comparative Example 1 controlled the copper-aluminum diffusion depth without controlling the surface roughness, resulting in the diffusion depth not changing much compared with the embodiment, but because the focus of the present invention is to study the heat cycle resistance of the substrate based on the three key conditions of roughness / copper-aluminum diffusion depth / etching size, Comparative Example 1 is insufficient in reliability, and in the later heat cycle resistance experiment, it can be seen that there is no stress release structure, the copper-aluminum bonding strength is poor, and the edge stress accumulation failure; Comparative Example 2 adopts the traditional direct pressing and sintering method to prepare a direct aluminum-coated ceramic substrate, and the copper-aluminum reaction diffusion depth cannot be controlled, a brittle intermediate layer is generated, and the thermal cycle fails.
[0052] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for improving the heat cycle reliability of a directly bonded aluminum-copper ceramic substrate, characterized in that: The following steps are involved: Step 1: Take a double-sided bonded aluminum ceramic substrate, perform surface roughness treatment, clean and dry it, and record it as substrate A, and the surface roughness Ra is 0.8mm~1.2μm; take a high-purity copper sheet, perform surface roughness treatment, clean and dry it, and record it as copper sheet B, and the surface roughness Ra is 1.0mm~2.0μm; Step 2: The substrate A and copper sheet B prepared in step 1 are stacked in the form of a copper sheet B-substrate A-copper sheet B sandwich, placed in a resistance diffusion welding machine, and voltage is applied to the surface of the copper sheet B with a vertical pressure of 5-10 MPa. When the temperature of the copper sheet B reaches 350°C-430°C, the voltage is maintained for 20-60 minutes, and then pressurized until the temperature of the copper sheet B reaches 450°C-557°C, the voltage is maintained for 10-60 minutes, the voltage is cut off, and the substrate is cooled to obtain a directly bonded aluminum-copper ceramic substrate; Step 3: Take the directly bonded aluminum-copper ceramic substrate prepared in step 2 and carry out surface laying of a photosensitive film, pattern exposure, development, metal layer etching, film removal, laser slicing, cleaning and drying; The depth of the reaction diffusion layer of copper and aluminum in the direct bonding aluminum-copper ceramic substrate in step 2 is 10-25 μm.
2. A method for improving the heat cycle reliability of a directly bonded aluminum-copper ceramic substrate according to claim 1, characterized in that: In step 1, the ceramic thickness of the double-sided bonded aluminum-ceramic substrate is 0.635 mm, 0.38 mm or 1.0 mm, the thickness of the aluminum layer is 0.2-0.8 mm, and the thickness difference of the double-sided bonded aluminum layer is less than 0.2 mm.
3. The method for improving the heat cycle reliability of a directly bonded aluminum-copper ceramic substrate according to claim 1, characterized in that: In step 1, the double-sided bonded aluminum ceramic substrate is subjected to surface roughness treatment, firstly subjected to grinding treatment or sandblasting treatment, and then the treated double-sided bonded aluminum ceramic substrate is placed in a sodium hydroxide solution for cleaning for 3 to 5 minutes, then transferred to a nitric acid solution for cleaning for 1 to 3 minutes, then taken out and placed in pure water for ultrasonic treatment for 1 to 5 minutes, and then dried.
4. The method for improving the heat cycle reliability of a directly bonded aluminum-copper ceramic substrate according to claim 1, characterized in that: In step 1, the thickness of the high-purity copper sheet is 0.2-0.8 mm, and the surface roughness is treated by grinding or sandblasting, and then the treated high-purity copper sheet is placed in a sulfuric acid solution for cleaning and drying.
5. The method for improving the heat cycle reliability of a directly bonded aluminum-copper ceramic substrate according to claim 1, characterized in that: The heating rate of the copper sheet B caused by pressurization in step 2 is 10-25°C / min.
6. The method for improving the heat cycle reliability of a directly bonded aluminum-copper ceramic substrate according to claim 1, characterized in that: In step 3, the etching solution used for etching the metal layer is prepared by dissolving ferric chloride and hydrochloric acid in pure water, wherein the concentration of ferric chloride is 150-500 g / L and the concentration of hydrochloric acid is 20-60 g / L; the cleaning is carried out using a 3-5% sulfuric acid solution and ultrasonic cleaning is performed for 3-5 minutes.
7. The method for improving the heat cycle reliability of a directly bonded aluminum-copper ceramic substrate according to claim 1, characterized in that: In step 3, the metal layer is etched to obtain an inverted trapezoidal structure of the etched groove, wherein the distance between the bottom edge of the aluminum layer and the edge of the ceramic is 0.1-0.3 mm, and the distance between the bottom edge of the copper layer and the top edge of the aluminum layer is 0.1-0.5 mm.
Citation Information
Patent Citations
Substrate unit for power modules, and power module
CN106463477A
Insulated circuit board
CN111771275A